Exposure to volatile DBPs in the indoor atmosphere of swimming pool facilities - Żak, Magdalena (Instal, 2022)
Swimming is one of the most commonly recommended forms of physical activity that positively affects the overall fitness of the entire body. However, it is necessary to keep in mind the possible health risks associated with the methods used to disinfect pool water leading to the formation of numerous disinfection by-products (DBPs). They are mostly present in the water, but also, with regard to highly volatile compounds, in the air of the swimming pool halls. Many of these compounds are characterized by very harmful health effects, for example, due to confirmed or potential carcinogenic, mutagenic, genotoxic properties or negative effects on various organs. This article presents an extensive literature review on the types of volatile DBP present in the atmosphere of swimming pools, especially trihalomethanes and chloramines, their precursors and causes of formation. A characterization of these compounds and a description of possible routes of exposure and the resulting health effects, with particular emphasis on inhalation exposure, are presented in the article.
Keywords: swimming pools; disinfection by-products; trihalomethanes; chloramines; indoor air health risks